Antioxidant Activity, LC-MS/MS Identification and In Silico Analysis of the Ethanol Extract of Beneng Taro Leaves (Xanthosoma undipes K. Koch) Grown in Three Different Locations - Diana Widiastuti,; Rudi Dwi Hariyanto,; Siska Elisahbet Sinaga,; Wira Eka Putra,; Sustiprijatno,; Ifa Manzila,; M Ace Suhendar,; Triastinurmiatiningsih,; Surya Diantina, (Tropical Life Sciences Research, 2026)
Xanthosoma undipes K. Koch (Beneng taro) leaves are rich in bioactive compounds with reported antioxidant and anticancer potential. This study evaluated the antioxidant activity of ethanol extracts from Beneng taro leaves cultivated in three locations, identified active compounds using liquid chromatography–tandem mass spectrometry (LC-MS/MS), and assessed their anticancer potential through in silico analysis. Extraction was performed with 96% ethanol, followed by phytochemical screening, quantification of total flavonoids and phenolics, and antioxidant evaluation using the DPPH assay. LC-MS/MS identified several bioactive phenolic and flavonoid compounds, including quercetin, isorhamnetin, hispidulin, oleocanthal and cyclovalone, as key contributors to antioxidant activity. Leaves from high-altitude Cisarua (TB-1) had the highest flavonoid (94.49 ± 1.61 mg QE/g) and phenolic (97.35 ± 1.74 mg GAE/g) contents, with the strongest antioxidant activity (IC₅₀ = 42.96 μg/mL). Drug-likeness screening indicated favourable pharmacokinetic properties for several compounds. Molecular docking revealed strong binding affinities of quercetin, isorhamnetin, hispidulin, cochliophilin A, cyclovalone and oleocanthal to Kirsten rat sarcoma viral oncogene homolog (KRAS), a key oncogenic protein regulating cell growth, division and mutation, suggesting potential anticancer effects. These findings indicate that cultivation at higher altitudes enhances bioactive compound levels and antioxidant potential. Future studies should isolate active compounds, validate their effects in vivo, optimise cultivation practices, and explore their development into functional foods or nutraceuticals.